Clinical Features, Diagnosis, and Treatment Strategies of Gastrointestinal Diaphragm Disease Associated with Nonsteroidal Anti-Inflammatory Drugs - Yan-Zhi Wang; Gang Sun; Feng-Chun Cai; Yun-Sheng Yang (Gastroenterology Research and Practice)
Background. To demonstrate the clinical features, diagnosis, and treatment of nonsteroidal anti-inflammatory drug- (NSAID-) induced diaphragm disease (DD). Methods. A literature search between January 1973 and August 2015 was undertaken. The clinical data of patients with NSAID-induced DD were recorded and analyzed. Results. 159 patients were included. The ratio of male to female was 1 : 2.3; the mean age was 65±11 years. The most common clinical manifestations were gastrointestinal bleeding and obstruction. 121 (84%) patients took traditional NSAIDs. The durations of NSAIDs use ranged from 2 to 300 months. A majority (59.7%) of DD were seen in the small bowel, were seen secondly in the colon (30.2%), and were mainly located in the ileum (57.9%) and right colon (91.7%), respectively. 80% of patients had multiple diaphragms. 41.5% of small bowel DD were diagnosed preoperatively by capsule endoscopy and/or double-balloon enteroscopy, 52.1% at laparotomy. Nearly 75% of patients underwent surgery, endoscopic balloon dilation was performed in 22 patients, and NSAIDs were withdrawn in 53 patients. Conclusions. NSAID-induced DD is relatively rare. The small bowel is most commonly involved. Preoperative diagnosis of small bowel DD is relatively difficult. Discontinuation of the NSAIDs is recommended, surgical resection is the main treatment presently, and endoscopic balloon dilation should be considered as an alternative therapy.